2022
DOI: 10.3389/fonc.2022.1046087
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of tumor size reduction assessed by magnetic resonance imaging after radiochemotherapy in patients with locally advanced cervical cancer

Abstract: ObjectivePelvic magnetic resonance imaging (MRI) is a key exam used for the initial assessment of loco-regional involvement of cervical cancer. In patients with locally advanced cervical cancer, MRI is used to evaluate the early response to radiochemotherapy before image-guided brachytherapy, the prognostic impact of which we aimed to study.MethodsPatients with locally advanced cervical cancer treated using concomitant radiochemotherapy followed by closure treatment between January 2010 and December 2015 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Several studies have shown that tumor reduction determined on MRI during EBRT was a significant prognostic factor ( 6 , 7 , 16 , 17 ). Most of these studies used treatment without CS and reported a cutoff value of 80–90% tumor volume reduction during EBRT of 45–50 Gy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that tumor reduction determined on MRI during EBRT was a significant prognostic factor ( 6 , 7 , 16 , 17 ). Most of these studies used treatment without CS and reported a cutoff value of 80–90% tumor volume reduction during EBRT of 45–50 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, tumor reduction during EBRT has been reported to be a prognostic factor (5)(6)(7). Tumor volume at diagnosis and its reduction during EBRT could be crucial factors in appropriate dose delivery in IGABT.…”
Section: Introductionmentioning
confidence: 99%
“…This adaptive target volume concept was developed to reflect tumor shrinkage at the end of initial chemoradiation and serves for an image-guided boost delivered through BT. [31,32] According to the analysis by Liu et al, [33] in domestic and foreign published literature related to ISBRT research, about 36% of the units use image-guided 3D-IGBT, CT is still the main guidance method, accounting for about 58%, MRI image guidance has made rapid progress, accounting for about 27% of image guidance, and the rest use X-ray or ultrasound guidance. Traditional CT-guided IGBT treatment requires multiple CT scans, increasing patient radiation dose.…”
Section: Discussionmentioning
confidence: 99%
“…This adaptive target volume concept was developed to reflect tumor shrinkage at the end of initial chemoradiation and serves for an image-guided boost delivered through BT. [ 31 , 32 ]…”
Section: Discussionmentioning
confidence: 99%